Equitable collaboration between LMIC and HIC researchers, part I: a preliminary framework for capacity building in psychiatric genetics research : perspective - Cabrera-Mendoza, Brenda; Burmeister, Margit; Rietschel, Marcella; Crepaz-Keay, David; Balhara, Yatan Pal Singh; Seedat, Soraya; Marshe, Victoria; Hemmings, Sian; Peterson, Roseann; Kaushik, Ruchika; Viswanath, Biju; Sud, Reeteka; et al. (American journal of medical genetics. Part B, Neuropsychiatric genetics, 2025)
International collaborations between high-income countries (HICs) and low- and middle-income countries (LMICs) have become increasingly essential in advancing global health, particularly within psychiatric research. These partnerships not only accelerate scientific discovery and enhance public health, but they also bring to light significant challenges in equity and fairness. Specifically, research partnerships often suffer from imbalances, such as “helicopter” research approaches or the exploitation and marginalization of LMIC researchers. Here, we present a consensus report by members of the International Society for Psychiatric Genetics, outlining key considerations and strategies for planning, implementing, and disseminating equitable collaborative research. Throughout the collaboration process, we identified both challenges and opportunities and provided recommendations to maximize the benefits of these partnerships. Among our considerations, we emphasize that Equitable Collaboration must begin with comprehensive stakeholder engagement, fostering a participatory environment that includes local communities, governments, and institutions from both HICs and LMICs. Among the potential challenges we identify are differences in ethical research and data-sharing frameworks across countries, inequalities in research resources and infrastructure, and reduced visibility of research conducted in LMICs. These factors can significantly impact research outcomes and their applicability. In conclusion, while global collaboration in psychiatric genetics presents complex challenges, it also offers substantial opportunities for impactful research and improved global mental health.
Erstmals veröffentlicht: 10. Juli 2025
Gesehen am 28.08.2025